(untitled) (International Journal of Studies in Nursing, 2019)
The purpose of this study was to understand the correlation between the elderly with depressive symptomatology and the predictors of the risk of violence against them. The method used was a quantitative approach using the Statistical Package program for Social Sciences. There was a participation of 237 elderly people aged 65-96 years, of the project “Aging in Safety in Alentejo-Understanding to Act”, at the University of Évora. The Geriatric Depression Scale and the Predictors of Risk of Violence (an adaptation of the Elder Abuse and Neglect-Risk Assessment Tool and Vulnerability to Abuse Screening Scale) were applied. About the results, 50 elderly (21.1%) had mild depressive symptomatology, and 14 (5.9%) had severe depressive symptomatology. Of the 64 elderly individuals who presented depressive symptomatology 55 were female. In the relationship between the severity of depressive symptomatology and predictors of risk of violence, significant results were found in three dimensions: current supports and relationships, family context and cognitive/emotional difficulties. The main conclusion of the study is that factors like no social support networks, complex family context and cognitive and emotional changes, contribute to greater physical and mental vulnerability of the elderly, resulting in cases of anxiety and stress, which present a depressive symptomatology and the risk of violence.